Advancements in the preparation methods of artificial cell membranes with lipids. (2nd June 2021) - Yuan, Wei; Piao, Jiafang; Dong, Yuanchen
Abstract : In order to better understand the structure and function of biological cell membranes, various artificial systems have been developed. Abstract : In order to better understand the structure and function of biological cell membranes, various artificial systems have been developed. Among them, unilamellar lipid vesicle (liposome)-based artificial cell membranes have attracted great interest due to their inherently similar structure and compositions to cellular membranes. Diverse methodologies, including film hydration methods, emulsion templated technologies and FGA strategies, have been well established for simulating the cell membrane structure. In this review, advancements in the preparation methods of unilamellar liposomes will be summarized, and the applications, advantages and challenges of each method will also be discussed.